Analisis Faktor-Faktor Yang Mempengaruhi Penggunaan Mobile Banking Syariah - Dewi, Annisa Elyana; Santosa, Purbayu Budi (BISNIS, 2024)
One of the biggest challenges that islamic mobile banking is facing today is that the numberof users is far less than that of conventional mobile banking. This research aims to analyzethe influence of the modified UTAUT 2 model’s factors on the use of islamic mobile banking.The research population is muslim Generation Z who are users of islamic mobile banking inSemarang, filtered into 100 samples using purposive sampling approach. The data collectionmethod is questionnaire using Likert scale measurement. The analysis technique used in thisstudy is Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS 3application. The results show that the intention of muslim Generation Z in Semarang to useislamic mobile banking is positively and significantly influenced by Performance Expectancy,Hedonic Motivation, Price Value, Habit, Perceived Credibility, and Religiosity, but not influencedby Effort Expectancy, Social Influence, and Facilitating Conditions. The results also find thatHabit and Behavioral Intention affect the actual use of islamic mobile banking positively andsignificantly, while Facilitating Conditions has no influence at all. The implication of this studyis for islamic banks to evaluate the development and maximization of the important factorsof islamic mobile banking to increase competitive advantage in facing financial technologyinnovation competitionSalah satu tantangan terbesar yang dihadapi mobile banking syariah saat ini adalah jumlah pengguna yang jauh lebih sedikit dibandingkan mobile banking konvensional. Menguji dan menganalisis pengaruh faktor-faktor model UTAUT 2 yang dimodifikasi terhadap penggunaan mobile banking syariah pada nasabah menjadi fokus dan tujuan utama penelitian. Populasi penelitian adalah Generasi Z muslim pengguna mobile banking syariah di Kota Semarang yang disaring menjadi 100 sampel melalui pendekatan sampling purposive. Data dikumpulkan melalui kuesioner yang diukur menggunakan skala likert. Teknik analisis yang digunakan dalam penelitian adalah Partial Least Squares-Structural Equation Modelling (PLS-SEM) menggunakan aplikasi SmartPLS 3. Hasil penelitian menunjukkan niat Generasi Z muslim di Kota Semarang untuk menggunakan mobile banking syariah secara positif signifikan dipengaruhi oleh Performance Expectancy, Hedonic Motivation, Price Value, Habit, Perceived Credibility, dan Religiusitas, tapi tidak dipengaruhi Effort Expectancy, Social Influence, dan Facilitating Conditions. Ditemukan pula bahwa Habit dan Behavioral Intention berpengaruh positif dan signifikan terhadap penggunaan aktual mobile banking syariah, sementara Facilitating Conditions tidak berpengaruh sama sekali.